The Lady of Lynn - Besant, Walter, 1836-1901 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Lady of Lynn" by Sir Walter Besant is a historical novel written in the late 19th century. The narrative is set in 18th-century England and revolves around the life of the protagonist, Jack Pentecrosse, who is appointed as the chief officer on the ship named after the titular character, The Lady of Lynn. The story explores themes of ambition, love, and societal expectations, particularly through the interactions between Jack and Molly Miller, the ship$1 (Bs young heiress. The opening of "The Lady of Lynn" introduces us to Jack Pentecrosse on his nineteenth birthday, marking a significant moment as he is promoted to chief officer aboard his ship. As we are drawn into his responsibilities at sea, we learn about the ship's owner, Molly Miller, and her wealth, which raises questions about her future and the romantic potential between her and Jack. The narrative also hints at larger societal dynamics, including issues of class disparity and ambition through the lens of Jack$1 (Bs humble origins as he navigates a world rife with expectations and traditions. The detailed descriptions of life at sea and the personal connections established create a rich backdrop for the unfolding drama, setting the stage for the characters' development and future challenges. (This is an automatically generated summary.)s
Release date is 2013-04-29
E-text prepared by sp1nd and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Historical fiction; Conspiracies -- Fiction; Health resorts -- Fiction; Sailors -- Fiction; Heiresses -- Fiction; Norfolk (England) -- Fiction